AB0757 Achievement of A Combined Clinical and Radiographic Endpoint in Patients with Psoriatic Arthritis in the ADEPT Trial. (10th June 2014) - Mease, P.; Karunaratne, P.M.; Kupper, H.; Hojnik, M.; Dorr, A.P.; McInnes, I.
Abstract : Background: Minimal disease activity (MDA) criteria for psoriatic arthritis (PsA) treatment encompass clinical aspects of PsA including arthritis, psoriasis, enthesitis, pain, patient assessment of disease activity, and physical function. Radiographic changes impact future functional status and as such, a measure of radiographic structural damage may be a meaningful addition to MDA as a composite treatment target. Objectives: To evaluate a composite endpoint including MDA and low radiographic progression in patients (pts) with PsA treated with adalimumab (ADA) Methods: In ADEPT (NCT00646386 ), pts with moderately to severely active PsA were randomized to receive ADA or placebo (PBO) for 24 weeks. Radiographs of hands and feet were obtained at baseline (BL) and wk 24. In this post hoc analysis, the proportion of pts achieving clinical endpoints of MDA 1, DAS28 <2.6 (DAS remission) and DAS28 <3.2 (DAS low disease activity [LDA]) were evaluated. The proportion of pts achieving low radiographic progression defined as mean change from BL in modified total Sharp score (ΔmTSS) ≤0.5 was evaluated. Results: At wk 24, data were available for 121 pts (ADA 61, PBO 60). At wk 24, 39% of ADA-treated pts achieved MDA (Table 1 ) compared to 7% of PBO-treated pts, similar to frequencies observed in pts achieving DAS28 remission. DAS28 LDA was achieved by 44% of ADA-treated pts vs. 12% of PBO pts. ΔmTSS ≤0.5 was achieved at wk 24 by 84% of ADA-treated pts and 60% of PBO pts. 34.4% (21/61) of ADA-treated pts achieved both MDA + ΔmTSS ≤0.5 vs. 6.7% (4/60) of PBO pts. Pts achieving MDA had less radiographic progression (Table 2 ). Pts achieving MDA, with or without low radiographic progression, had lower baseline joint counts and HAQ scores than those who did not achieve MDA. Conclusions: In this analysis, the addition of low radiographic progression to MDA, DAS28 remission, or DAS28 LDA appeared to increase the stringency of the endpoint achieved on anti-TNF therapy in PsA pts. Further analysis is needed to determine whether this novel composite endpoint translates into long-term pt benefits. References: Mease P et al. J Rheumatol. First Release March 15 2013; doi:10.3899/jrheum.120970. Acknowledgements: AbbVie funded the study (NCT00646386 ), contributed to its design and was involved in the collection, analysis, and interpretation of the data, and in the writing, review, and approval of the publication. Medical writing support was provided by Kathleen V. Kastenholz, PharmD, MS, of AbbVie. Disclosure of Interest: P. Mease Grant/research support: AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex, Consultant for: AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex, Speakers bureau: AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex, P. Karunaratne Shareholder of: AbbVie, Employee of: AbbVie, H. Kupper Shareholder of: AbbVie, Employee of: AbbVie, M. Hojnik Shareholder of: AbbVie, Employee of: AbbVie, A. Dorr Shareholder of: AbbVie, Employee of: AbbVie, I. McInnes Grant/research support: AbbVie, Amgen, Janssen, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, Janssen, Novartis, Pfizer, and UCB DOI: 10.1136/annrheumdis-2014-eular.1431